An ANALYSIS OF TEACHERS’ CREATIVITY IN MEDIA-BASED LEARNING GRADE X AT SMK PENCAWAN MEDAN - Likawati Doloksaribu; Epria Primsa Meliala; Pebri Wati Romatua Purba; Lavia Panjaitan (elt, 2020)
ABSTRACT This study aims to describe the creativity of English teachers when SMK Pencawan Medan grade X use learning media. This research is descriptive. The data is obtained through interviews. The data analysis followed some steps, namely collecting data, reducing, display data, data verification and create reports. The results showed that teachers employed the various teaching-learning media in ELT classes. English teachers used various media to make it easier for students to learn and understand the teaching materials. The media include audio, visual, and audio visual. The most media used in the ELT classes were audio and visual. A small part of the media is produced through internet sources. However, the teacher’s implementation method is not optimal. This can be seen from the imperfect application of the PowerPoint medium when the teacher uses the power point medium. Not every day teachers use the learning medium to achieve their learning goals. Based on the conclusion above, the researchers give suggestion to the teachers should always looking for creative new things and create active, innovative, and fun learning, and also motivate students to seriously participate in learning even though they study through online. Keywords : Creativity, Learning media